The effectiveness of advertising channel in Muar district office / Nur Fadzillah Yacob - Yacob, Nur Fadzillah (2018)
This study aims to effectiveness of advertising in an organization. The independent variables for the study are awareness of advertising, comprehension of product and conviction of purchase. Data were collected from 80 respondents from employees and clients-of Muar District Office via convenience sampling method. The collected data were keyed in into Statistical Software Package for Social Science (SPSS) and analysed using various method such as Frequency Analysis, Descriptive Analysis, Reliability Analysis, Pearson Correlation and Multiple Regression Analysis. The results of the study found that all variables have positive relationship with effectiveness advertising channel and AIDA model. The findings of this research will be useful for organization who intend to enhance advertising in the organization.